2005
DOI: 10.1016/j.humimm.2004.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of monocyte/macrophage function by human CD4+CD25+ regulatory T cells

Abstract: The suppressive effects of CD4+CD25+ regulatory T cells (Tregs) on T cells have been well documented. Here we investigated whether human CD4+CD25+ Tregs can inhibit the proinflammatory properties of monocytes/macrophages. Monocytes and T cells were isolated from peripheral blood of healthy volunteers by magnetic cell separation and cocultured for 40 h. Monocytes were analyzed directly for cytokine production and phenotypic changes or repurified and used in T-cell stimulation and lipopolysaccharide challenge as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(182 citation statements)
references
References 38 publications
8
169
0
5
Order By: Relevance
“…Correlating with the thickened vessel wall, the infiltrated inflammatory cells in the vessel from Bax Tg after cuff placement were significantly higher than that in wild-type mice ( Figure 6C4). Since it has been reported that CD4+CD25+ Tregs can exert direct suppressive effects on monocytes/macrophages in addition to suppressing effector T cells (33), therefore, our results suggest that the higher expression of Bax in Tregs reduces the striking threshold of inflammatory pathogenesis of vasculitis due to higher rates of Treg apoptosis and presumably failure in suppressing inflammatory cells ( Figure 6D). …”
Section: Higher Expression Of Bax In Tregs Lowers Striking Threshold mentioning
confidence: 60%
“…Correlating with the thickened vessel wall, the infiltrated inflammatory cells in the vessel from Bax Tg after cuff placement were significantly higher than that in wild-type mice ( Figure 6C4). Since it has been reported that CD4+CD25+ Tregs can exert direct suppressive effects on monocytes/macrophages in addition to suppressing effector T cells (33), therefore, our results suggest that the higher expression of Bax in Tregs reduces the striking threshold of inflammatory pathogenesis of vasculitis due to higher rates of Treg apoptosis and presumably failure in suppressing inflammatory cells ( Figure 6D). …”
Section: Higher Expression Of Bax In Tregs Lowers Striking Threshold mentioning
confidence: 60%
“…CD4ϩ,CD25ϩ Treg cells have been shown to inhibit T cell proliferation, cytokine production, autoantibody production, and dendritic cell and monocyte/ macrophage function (1)(2)(3)(4)(5)(6). Recent studies suggest that their function is defective in certain human autoimmune diseases (7), including multiple sclerosis (8), type 1 diabetes mellitus (9), and rheumatoid arthritis (RA) (10).…”
mentioning
confidence: 99%
“…Indeed, recent findings indicate, that these M/M are also able to induce Tregs, which additionally account for the drastically reduced T cell proliferation induced by the M/M [45]. Vice versa, Tregs respond to M/M since they are able to block M/M maturation [46]. Thus, these data indicate that alternatively activated M/M can induce immunosuppressive Tregs and that in return these Tregs are potent suppressors of M/M maturation.…”
Section: Impaired Cd4 + /Foxp3 + Regulatory T Cell Function In Patienmentioning
confidence: 76%